Sistem Pendukung Keputusan Penentuan Siswa Bermasalah Menggunakan Metode Simple Additive Weighting (SAW) Pada Mts Ath-Thohiriyah - Muhandhis, Isnaini; Widhiyanta, Nurwahyudi; Aldo Ferdianto, Ananda (Journal of System Engineering and Technological Innovation, 2022)
Guidance and counseling have a big role in helping students in schools achieve the goals of holding education. At MTs Ath-Thohiriyah, the counseling teacher recorded the condition of the students manually, using paper media as recording and storing data. With these data, the teacher still has difficulty in determining the condition of each student because there is no definite assessment that the student needs guidance or not. Based on this problem, this study aims to create a decision support system that is expected to be able to help provide information and references to determine priorities for determining problematic students. The method used to determine the ranking of problematic students is Simple Additive Weighting (SAW). The results of this study, the SAW method can be used to determine problematic students at MTs Ath-Thohiriyah with four criteria including knowledge, skills, social and spiritual. The application made in this study is able to help BK teachers in registering students at school and determining students who need guidance